Infidel or Paganus?: The Polysemy of "kafara" in the Quran - Cole, Juan Ricardo (JAOS, 2020)
This article explores the meaning of the root k-f-r in the Quran, questioning the practice of translating the noun kāfir as "infidel." It argues for a distinction between the idiomatic phrasal verb kafara bi-, which does mean to reject or disbelieve, and the simple intransitive verb kafara and its deverbal nouns, which are used in the Quran in a large number of different ways. This polysemy is explored through contextual readings of Quran passages. It is argued that the noun kāfir, unlike the verb kafara, is used only with regard to adherents of traditional polytheism and is not deployed in an unmodified way with regard to Jews and Christians. The possible influence on the Arabic kafara of Greek and Latin conceptions is also broached.